“The use of Interest Rate Derivatives by non-financial Firms” - Honavar, Gaurav (2015)
The topic of discussion is the use of Interest Rate Derivatives by non-financial firms in the UK. The data of the non-financial firms is gathered from the information available in the financial statements. The objective of the study was to analyse how firms use floating rate debts or fixed rate debts to hedge their interest rate risk. It is found that bank debts for nonfinancial firms is set on a floating rate, firms with higher cash holdings choose to have more floating rate debt, firms with high leverage prefer to have fixed rate debts, firms manage the volatility in their earnings before interest and tax (EBIT) using floating rate debts and firms with credit ratings usually desire for a fixed rate debt. The findings for these independent variables is found to be consistent with existing literature. However, tests for the effects of firm size, short-term debt and long-term debts on the floating rate debt were futile since they did not yield statistically significant results.